Bilobed ﬂap for the reconstruction of lower eyelid defect: a case report - Rogerio Nabor Kondo; Nathalia Elisa Rosolen e Silva; Nicole Camila D’Aquila Gonçalves; Cássio Rafael Moreira (Surgical & Cosmetic Dermatology, 2023)
Merkel cell carcinoma is a rare and aggressive cutaneous neuroendocrine cancer that occurs in the photodamaged skin of white and elderly patients, usually presenting as a solitary plaque or nodule in the head and neck region. When located in the lower palpebral area, reconstructing the defect resulting from its excision can become challenging for the dermatological surgeon due to the local cosmetic and functional peculiarity. We report the use of a bilobed ﬂap for lower eyelid reconstruction with a satisfactory result, both in terms of aesthetics and the resulting functionality.